Consumption of garlic positively affects hedonic perception of axillary body odour - Fialová, Jitka; Roberts, S Craig; Havlíček, Jan (Appetite, 2016)
Beneficial health properties of garlic, as well as its most common adverse effect - distinctive breath odour - are well-known. In contrast, analogous research on the effect of garlic on axillary odour is currently missing. Here, in three studies varying in the amount and nature of garlic provided (raw garlic in study 1 and 2, garlic capsules in study 3), we tested the effect of garlic consumption on the quality of axillary odour. A balanced within-subject experimental design was used. In total, 42 male odour donors were allocated to either a "garlic" or "non-garlic" condition, after which they wore axillary pads for 12 h to collect body odour. One week later, the conditions were reversed. Odour samples were then judged for their pleasantness, attractiveness, masculinity and intensity by 82 women. We found no significant differences in ratings of any characteristics in study 1. However, the odour of donors after an increased garlic dosage was assessed as significantly more pleasant, attractive and less intense (study 2), and more attractive and less intense in study 3. Our results indicate that garlic consumption may have positive effects on perceived body odour hedonicity, perhaps due to its health effects (e.g., antioxidant properties, antimicrobial activity).
Keywords: Allium sativum; Antioxidant; čichová percepce; Humans; index tělesné hmotnosti; Body Mass Index; Diet; Odorants; Female; mladý dospělý; dospělí; lidé; Sexual selection; česnek; Garlic; mužskost; odoranty; Health; Adult; ženské pohlaví; Male; Olfactory Perception; Young Adult; Body Weight; Masculinity; tělesná hmotnost; mužské pohlaví